2022
DOI: 10.2147/ppa.s370178
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Personal Cultural and Religious Beliefs on Medication Adherence among Patients with Chronic Diseases at University Hospital in Northwest Ethiopia 

Abstract: Background Subjective beliefs about chronic disease conditions and their drug management are among factors determining adherence to medications that are amenable to interventions. Patient-level factors such as personal, cultural, and religious beliefs about diseases, and medication use may have a significant impact on medication adherence. The purpose of this study was to assess the impact of personal, cultural and religious beliefs on medication adherence behavior among patients with chronic foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In LMICs, religion plays a significant role in daily life and it could be a challenging issue regarding non-adherence to medication due to the beliefs about the super power of God ( 98 ). People who place a high value on religion tend to share the view that God can and does perform miracles and has absolute control over everything in their lives ( 99 ).…”
Section: Discussionmentioning
confidence: 99%
“…In LMICs, religion plays a significant role in daily life and it could be a challenging issue regarding non-adherence to medication due to the beliefs about the super power of God ( 98 ). People who place a high value on religion tend to share the view that God can and does perform miracles and has absolute control over everything in their lives ( 99 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that adherence is positively correlated with health seeking, the relevance of any form of treatment for a patient is determined by their attitude. 24,48 It was additionally determined that the absence of involvement from family members predicted failure to adhere to psychotropic medications. Research from the United States and Nigeria agreed up this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that adherence is positively correlated with health seeking, the relevance of any form of treatment for a patient is determined by their attitude. 24 , 48 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kasahum et al [55] stated that "Subjective beliefs about chronic disease conditions and their drug management are among factors determining adherence to medications that are amenable to interventions." People's perceptions about their diseases, knowledge, and care are based on their environment or setting [1] A study in Ethiopia about the impact of personal, cultural and religious beliefs on medication on patients with chronic disease [55] concluded that personal beliefs were significantly associated with low medication adherence and that study participants with stronger beliefs in the efficacy of traditional medicine were less likely to adhere to their medications. Differences in the culture of the patient and care giver could be an impediment in chronic disease care [46].…”
Section: ) Health Literacy and Awarenessmentioning
confidence: 99%